A parametric study of accelerated carbonation in alkali-activated slag. (July 2021) - McCaslin, Eric R.; White, Claire E.
Abstract: Resistance to carbonation is one important attribute that low-CO2 cement alternatives must possess, and is particularly crucial for cement alternatives subjected to aggressive CO2 concentrations such as those used in construction of oil wells and wells for below ground carbon sequestration. Here, a parametric study of alkali-activated slag (AAS) carbonation in aggressive environments has been conducted to examine (i) calcium carbonate polymorphism using X-ray diffraction (XRD) and Fourier-transform infrared (FTIR) spectroscopy, and (ii) the extent of calcium carbonate formation and CO2 adsorption using thermogravimetric analysis (TGA). A range of AASs have been studied by varying the magnesium content of the slag, the activator type (sodium hydroxide and sodium silicate), the activator concentration, and the curing time prior to carbonation. It was uncovered that both (i) magnesium from the slag and (ii) silica from the activating solution are needed to reduce the propensity for the sodium-containing calcium-alumino-silicate-hydrate gel to undergo decalcification.